A Study of Hot and Cold Metaphors in Iraqi Arabic - Jabber, Khalid Wahaab; Al-Saedi, Hayder Tuama Jasim (REiLA : Journal of Research and Innovation in Language, 2020)
The present study is an attempt to explore the ways of an Iraqi Arabic speaker conceptualises his/her understanding of various abstract domains of emotions or feeling and attitudes through his/her experiences of concrete domains of Cold and Hot metaphors. Lakoff & Johnson’s (1980) Conceptual Metaphor Theory is adopted to analyse the collected data. Idiomatic expressions and proverbs are chosen specifically from the southern dialect where they are widely used in daily interaction. The data analysis classified the results according to their abstract and concrete domains of the sampled data. The findings of this study showed different conceptualisations of the Hot and Cold metaphor in Iraqi Arabic. The study concluded that these metaphors are used to conceive more of the abstract concepts of emotions, feelings, and attitudes. Cold domain is used to conceptualise the bad habits of people, and it is also used to conceptualise some good habits, on the other hand. Whereas Hot domain is used to conceptualise the more intensive of emotions and attitudes. The study concluded that the sharp emotions, feelings and attitudes that are understood from the conceptualisation of Hot and Cold conceptual metaphors, are experienced from the more concrete domains of hard things.